Apertura comercial y su efecto en el empleo de un país en vía de desarrollo: el caso peruano - Bravo-Ambrocio, Linda (2024)
The purpose of this study is to determine whether the trade liberalization process that Peru began around 2008 has influenced labor demand in line with the expectations of neoclassical theory. Considering Peru’s specificities, it would be anticipated that: 1) employment would increase due to the rise in production and the surge in labor intensity, 2) there would be a redistribution of resources from less competitive sectors to those where Peru has comparative advantages, and 3) there would be a higher generation of employment in sectors predominantly requiring unskilled labor. Using data from the BCRP and Electronic Payroll, it was observed that from 2008 to 2019, there was an increase both of exports and imports with their effects on the production. However, in certain manufacturing areas, especially those aimed at exportation, a stronger correlation between product and employment was noticed. The labor redistribution among sectors became evident due to an increase in the production of goods demanding labor.